2019
DOI: 10.1021/acs.jpclett.9b00623
|View full text |Cite
|
Sign up to set email alerts
|

Aromaticity and Antiaromaticity in the Excited States of Porphyrin Nanorings

Abstract: Aromaticity can be a useful concept for predicting the behavior of excited states. Here we show that π-conjugated porphyrin nanorings exhibit size-dependent excited-state global aromaticity and antiaromaticity for rings containing up to eight porphyrin subunits, although they have no significant global aromaticity in their neutral singlet ground states. Applying Baird’s rule, even rings ([4n] π-electrons) are aromatic in their lowest excited states, whereas the lowest excited states of odd rings ([4n + 2] π-el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
66
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 56 publications
(117 reference statements)
0
66
0
1
Order By: Relevance
“…[13] Electronic excitation can lead to excited-state aromaticity, [4,14] and molecules such as c-P6 are aromatic in their lowest excited states. [15] Many other macrocycles with global aromaticity in the neutral, cationic,a nd excited states have been reported in the last decade. [16][17][18][19][20][21] Porphyrin oligomers have an exceptionally wide range of accessible oxidation states;f or example, c-P6·T6 can be reversibly oxidized up to the 12 + state and reduced to the 6À state.…”
mentioning
confidence: 99%
“…[13] Electronic excitation can lead to excited-state aromaticity, [4,14] and molecules such as c-P6 are aromatic in their lowest excited states. [15] Many other macrocycles with global aromaticity in the neutral, cationic,a nd excited states have been reported in the last decade. [16][17][18][19][20][21] Porphyrin oligomers have an exceptionally wide range of accessible oxidation states;f or example, c-P6·T6 can be reversibly oxidized up to the 12 + state and reduced to the 6À state.…”
mentioning
confidence: 99%
“…A number of questions can now be posed: It is known that the extent of Bairdaromaticity varies with computational method, 18 but how does it vary between the different macrocycles? Also, to what extent is there an agreement between various types of aromaticity indices on the magnitude of Baird-aromaticity of macrocycles?…”
Section: An Interesting Description Of Baird-aromaticity Is the Descrmentioning
confidence: 99%
“…Our focus is on the potential T1 state Baird- was observed that the extent of T1 state Baird-aromaticity assessed through computations varies strongly with choice of DFT functional. 18 On the other hand, for [n]cycloparaphenylene nanohoops ([n]CPP's) 19 , 20 , 21 -22 in their T1 states it has been considered that long-range corrected functionals are preferred. 23 When going to gradually larger [n]CPP's in their T1 states calculated with UCAM-B3LYP, structures changed from circular with fully delocalized triplet excitations to egg-shaped with the excitations localized to a subset of the para-phenylene units at n > 5.…”
Section: Introductionmentioning
confidence: 99%
“…( Anti)aromaticity can be induced by perturbing the electronic structure,f or example,b y oxidation or excitation. [15] Many other macrocycles with global aromaticity in the neutral, cationic,a nd excited states have been reported in the last decade. [9] Removal of 4or6electrons from the six-porphyrin nanoring c-P6·T6 leads to macrocyclic global antiaromaticity (80 pelectrons) or aromaticity (78 p-electrons), respectively.…”
mentioning
confidence: 99%